The Idea of Designing an Amphitheater in the Besh Qardash of Bojnord (Tourist Destination and Recreational Region) with Stretch Fabric Structures - Mojgan Ghorbanzadeh (Civil Engineering Journal, 2018)
One of the criteria for sustainable design is "the principle of adaptation to local regions".  In this case, the native, historical, cultural and specific characteristics of the region are considered. This study tried to use an idea of designing an amphitheater in the Besh Qardash of Bojnourd (tourist destination and recreational region) with stretch fabric structures as the contemporary structural systems that have a certain similarity to nomadic tents which along with being in line with the historical and cultural elements of the region, including the historical tomb next to the spring, present a combination of modern and local architecture. This can be a great help to hold ceremonies and cultural events in this location, such as holding traditional wrestling competitions (Ba Chukhe) and horse racing (Turkman horse) in special time of the year. In the following parts, along with introducing the geographical and climatic conditions of the region by examining the technical and executive characteristics of stretch fabric structures, the results will be presented.